2014
DOI: 10.1371/journal.pgen.1004248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Interphase Functions for the NIMA Kinase Involving Microtubules and the ESCRT Pathway

Abstract: The Never in Mitosis A (NIMA) kinase (the founding member of the Nek family of kinases) has been considered a mitotic specific kinase with nuclear restricted roles in the model fungus Aspergillus nidulans. By extending to A. nidulans the results of a synthetic lethal screen performed in Saccharomyces cerevisiae using the NIMA ortholog KIN3, we identified a conserved genetic interaction between nimA and genes encoding proteins of the Endosomal Sorting Complex Required for Transport (ESCRT) pathway. Absence of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 98 publications
(103 reference statements)
1
24
0
Order By: Relevance
“…For example, three Arabidopsis thaliana NEKs (related to NEKL-2) have been implicated in epidermal root tip growth through the possible regulation of microtubules (Sakai et al 2008;Motose et al 2011Motose et al , 2012. Perhaps most notable was the recent report that Aspergillus nidulans nimA, which was originally identified for its role in mitosis, also controls polarized cell growth and localizes to microtubule plus ends in an EB1-dependent manner during interphase (Govindaraghavan et al 2014). This study also showed that mutations in both the A. nidulans and Saccharomyces cerevisiae NIMA orthologs (nimA and kin3) are synthetically lethal with mutations in genes encoding ESCRT complex components, which promote membrane remodeling and endosome maturation (McCullough et al 2013;Govindaraghavan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, three Arabidopsis thaliana NEKs (related to NEKL-2) have been implicated in epidermal root tip growth through the possible regulation of microtubules (Sakai et al 2008;Motose et al 2011Motose et al , 2012. Perhaps most notable was the recent report that Aspergillus nidulans nimA, which was originally identified for its role in mitosis, also controls polarized cell growth and localizes to microtubule plus ends in an EB1-dependent manner during interphase (Govindaraghavan et al 2014). This study also showed that mutations in both the A. nidulans and Saccharomyces cerevisiae NIMA orthologs (nimA and kin3) are synthetically lethal with mutations in genes encoding ESCRT complex components, which promote membrane remodeling and endosome maturation (McCullough et al 2013;Govindaraghavan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most notable was the recent report that Aspergillus nidulans nimA, which was originally identified for its role in mitosis, also controls polarized cell growth and localizes to microtubule plus ends in an EB1-dependent manner during interphase (Govindaraghavan et al 2014). This study also showed that mutations in both the A. nidulans and Saccharomyces cerevisiae NIMA orthologs (nimA and kin3) are synthetically lethal with mutations in genes encoding ESCRT complex components, which promote membrane remodeling and endosome maturation (McCullough et al 2013;Govindaraghavan et al 2014). Although the functional connection between nimA and ESCRT proteins is unknown, this finding implicates NIMA kinases in processes linked to intracellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…The Set1 complex is essential when the function of NIMA or NIMT (and hence mitotic CDK1) is partially impaired By extending the results of a synthetic lethal screen conducted using the nonessential S. cerevisiae NIMA ortholog Kin3 to A. nidulans (Govindaraghavan et al 2014b), a genetic interaction was identified between NIMA and Answd1 (Figure 1), the gene encoding the A. nidulans ortholog of yeast Swd1, a WD40 repeat containing subunit of the Set1 methyltransferase complex, also called the COMPASS complex (locus AN0808; see http://www.aspergillusgenome.org/ cgi-bin/locus.pl?locus=AN0808). Deletion of An-swd1 generated haploid null strains having growth and conidiation defects that displayed cold sensitivity ( Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…A synthetic lethal screen was conducted using the deletion of the nonessential Saccharomyces cerevisiae NIMA ortholog Kin3 (Govindaraghavan et al 2014b). Here we reveal that the novel genetic interaction between nimA and the gene encoding a subunit of the Set1 protein methyltransferase complex (also called the COMPASS complex for Complex Proteins Associated with Set1) (Miller et al 2001) An-swd1 (Roguev et al 2001) is conserved in A. nidulans.…”
mentioning
confidence: 99%
“…On the other hand, we identified two protein kinases functionally characterized but with no known functions related to glycogen metabolism regulation. More recently, this kinase was demonstrated to regulate interphase microtubules, indicating that it could integrate cell growth and development with mitotic regulation in A. nidulans [43]. This protein kinase was first identified in S. cerevisiae as required in the meiotic cell cycle, but more recent studies revealed that this kinase displays multiple cellular functions beyond meiosis [41].…”
Section: Discussionmentioning
confidence: 99%